Biodegradation of food waste using microbial cultures producing thermostable α-amylase and cellulase under different pH and temperature. (January 2018) - Awasthi, Mukesh Kumar; Wong, Jonathan W.C.; Kumar, Sunil; Awasthi, Sanjeev Kumar; Wang, Quan; Wang, Meijing; Ren, Xiuna; Zhao, Junchao; Chen, Hongyu; Zhang, Zengqiang
Highlights: The amylase and cellulase producing bacteria were isolated from composts. The enzymes activities and stability were investigated. Maximum food waste degradation was observed employing bacterial consortium. Abstract: The aim of this work was to study the biodegradation of food waste employing thermostable α-amylase and cellulase enzymes producing bacteria. Four potential isolates were identified which were capable of producing maximum amylase and cellulase and belong to the amylolytic strains, Brevibacillus borstelensis and Bacillus licheniformis ; cellulolytic strains, Bacillus thuringiensis and Bacillus licheniformis, respectively. These strains were selected based on its higher cell density, enzymatic activities and stability at a wide range of pH and temperature compared to other strains. The results indicated that 1:1 ratio of pre and post consumed food wastes (FWs) were helpful to facilitate the degradation employing bacterial consortium. In addition, organic matter decomposition and chemical parameters of the end product quality also indicated that bacterial consortium was very effective for 1:1 ratio of FWs degradation as compared to the other treatments.